Knowledge, attitudes, and practices regarding intrinsic capacity in the elderly population: A cross-sectional study in Shanghai, China - Xu Zhou; Fei Gu; Zhirui Li; Yun Li; Xiao Liu; Xuan Liu; Tingting Huang (Scientific Reports)
Abstract To investigate the knowledge, attitudes, and practices (KAP) of the elderly population regarding their intrinsic capacity, as defined by the World Health Organization as a marker of healthy aging. A cross-sectional study was conducted at the Shanghai Traditional Chinese Medicine Hospital from July to November 2023. Participants’ socio-demographic information and KAP scores were collected through a self-designed questionnaire. A total of 507 elderly individuals participated, with 53.25% being male and a mean age of 70.76 ± 7.63 years. The mean knowledge, attitude, and practice scores were 19.58 ± 8.85, 30.07 ± 4.81, and 34.71 ± 7.77, respectively. Pearson’s correlation analysis showed significant positive correlations among the KAP scores (all P < 0.001). Multivariate logistic regression indicated that knowledge scores (OR = 1.127, P < 0.001), attitude scores (OR = 1.189, P < 0.001), and current employment status (OR = 2.759, P = 0.009) were associated with proactive practices. Structural equation modeling demonstrated that knowledge had a direct influence on attitude (β = 0.572, P < 0.001) and practice (β = 0.776, P < 0.001), while attitude directly impacted practice (β = 0.412, P < 0.001). The study reveals that the elderly lack knowledge but have positive attitudes and proactive behaviors about intrinsic capacity. Enhancing education and attitudes is vital for healthy aging and well-being.